SOSIALISASI DAN PENDAMPINGAN PENGGUNAAN APLIKASI SIKAGINTING (SISTEM INFORMASI KADER GIZI DAN STUNTING) SEBAGAI UPAYA PENCEGAHAN STUNTING PADA BALITA DI PUSKESMAS NAMBO KOTA KENDARI - Fifi Nirmala G; Rizal Adi Saputra; Nurmaladewi Nurmaladewi; Rizki Eka Sakti Octaviani; La Surimi (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2023)
Stunting is a chronic condition that describes stunted growth due to long-term malnutrition. Stunting according to the WHO Child Growth Standard is based on an index of body length for age (PB/A) or height for age (TB/A) with a z-score less than -2 SD (Beal et al., 2018). The prevalence of stunting in Southeast Sulawesi ranks fifth highest in cases of stunting in Indonesia. One of the cities contributing to stunting in Southeast Sulawesi is the city of Kendari. One of the areas with stunting cases that fall into the category of 5 areas with the highest cases of stunting in Kendari City in 2020 is Nambo District (0.16%) which is the working area of the Nambo Health Center (Kendari City Health Office, 2020). The Sikaginting application (Information System for Nutrition and Stunting Cadres) is an application for recording data on nutrition cadres and stunting prevention for Posyandu in the working area of Puskesmas Nambo. This application has a variety of features and advantages that can make it easier for nutrition cadres to collect data and handle stunting. With the Sikaginting application, it can help increase the effectiveness and efficiency of nutrition cadres in identifying existing cases of stunting so that treatment measures can be taken according to existing procedures.